Quercetin attenuates neuronal cells damage in a middle cerebral artery occlusion animal model - PARK, Dong-Ju; SHAH, Fawad-Ali; KOH, Phil-Ok (Journal of Veterinary Medical Science, 2018)
Cerebral ischemia is a neurological disorder with high mortality. Quercetin is a flavonoid compound that is abundant in vegetables and fruits. It exerts anti-inflammatory and anti-apoptotic effects. This study investigated the neuroprotective effects of quercetin in focal cerebral ischemia. Male Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO) to induce focal cerebral ischemia. Quercetin or vehicle was injected 30 min before the onset of ischemia. A neurological function test, brain edema measurement, and 2,3,5-triphenyltetrazolium chloride staining were performed to elucidate the neuroprotective effects of quercetin. Western blot analysis was performed to observe caspase-3 and poly ADP-ribose polymerase (PARP) protein expression. MCAO leads to severe neuronal deficits and increases brain edema and infarct volume. However, quercetin administration attenuated the MCAO-induced neuronal deficits and neuronal degeneration. We observed increases in caspase-3 and PARP protein levels in MCAO-operated animals injected with vehicle, whereas quercetin administration attenuated these increases in MCAO injury. This study reveals the neuroprotective effect of quercetin in an MCAO-induced animal model and demonstrates the regulation of caspase-3 and PARP expression by quercetin treatment. These results suggest that quercetin exerts a neuroprotective effect through preventing the MCAO-induced activation of apoptotic pathways affecting caspase-3 and PARP expression.